2017
DOI: 10.1364/boe.8.004640
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of skin inflammation using an oxygen-sensing paint-on bandage

Abstract: Inflammation involves a cascade of cellular and molecular mediators that ultimately lead to the infiltration of immune cells into the affected area. This inflammatory process in skin is common to many diseases including acne, infection, and psoriasis, with the presence or absence of immune cells a potential diagnostic marker. Here we show that skin inflammation can be non-invasively measured and mapped using a paint-on oxygen sensing bandage in an in vivo porcine inflammation model. After injection of a known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…However, the true pO 2 on the skin surface can only be measured by methods that do not consume oxygen during measurement. 45 Optical methods based on fluorescence-, 7 phosphorescence-, [8][9][10] or luminescence-quenching 11,12 and EPR, 32,46 including SPOT chip, do not use oxygen and hence are capable of reporting true skin pO 2 at ambient or physiological temperatures. For example, an oxygen optode device based on fluorescence lifetime imaging (FLIM), reported an average of ~ 20 mmHg of TcpO 2 in the medial lower leg of human subjects (N = 5) measured by heating the skin to 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…However, the true pO 2 on the skin surface can only be measured by methods that do not consume oxygen during measurement. 45 Optical methods based on fluorescence-, 7 phosphorescence-, [8][9][10] or luminescence-quenching 11,12 and EPR, 32,46 including SPOT chip, do not use oxygen and hence are capable of reporting true skin pO 2 at ambient or physiological temperatures. For example, an oxygen optode device based on fluorescence lifetime imaging (FLIM), reported an average of ~ 20 mmHg of TcpO 2 in the medial lower leg of human subjects (N = 5) measured by heating the skin to 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…These outliers were often acquired immediately after the application of Tegaderm to the newly reconstructed breast and may arise as a combination of reperfusion during flap uptake and equilibration of the bandage material with the living skin beneath. This equilibration effect has been observed and mathematically modeled in prior preclinical studies (51). This indicates that, while the calibration on ex vivo tissue model does not perfectly mimic each patient's in vivo environmental conditions and oxygen/Tegaderm barrier diffusion kinetics, the general trend still follows that of a standard NIRS oximeter.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, we have demonstrated that CFA is an adequate model to study cutaneous inflammation in large animals. The inflammatory reaction can be adequately assessed not only by histology, but noninvasively by simply measuring the induration of the lesions which can be accurately done when animals are injected subcutaneously [ 23 ]; or by the assessment of oxygen consumption in the lesions as we have previously reported [ 24 ]. Thus, this study provides evidence of the safe use of CFA in a humane manner when properly administered into the SC space.…”
Section: Discussionmentioning
confidence: 99%